Inferior long‐term outcomes of liver‐kidney transplantation using donation after cardiac death donors: Single‐center and organ procurement and transplantation network analyses. Issue 6 (June 2014) - Wadei, Hani M.; Bulatao, Ilynn G.; Gonwa, Thomas A.; Mai, Martin L.; Prendergast, Mary; Keaveny, Andrew P.; Rosser, Barry G.; Taner, C. Burcin
<x xml:space="preserve">Abstract</x> Limited data are available for outcomes of simultaneous liver‐kidney (SLK) transplantation using donation after cardiac death (DCD) donors. The outcomes of 12 DCD‐SLK transplants and 54 SLK transplants using donation after brain death (DBD) donors were retrospectively compared. The baseline demographics were similar for the DCD‐SLK and DBD‐SLK groups except for the higher liver donor risk index for the DCD‐SLK group (1.8 ± 0.4 versus 1.3 ± 0.4, P = 0.001). The rates of surgical complications and graft rejections within 1 year were comparable for the DCD‐SLK and DBD‐SLK groups. Delayed renal graft function was twice as common in the DCD‐SLK group. At 1 year, the serum creatinine levels and the iothalamate glomerular filtration rates were similar for the groups. The patient, liver graft, and kidney graft survival rates at 1 year were comparable for the groups (83.3%, 75.0%, and 82.5% for the DCD‐SLK group and 92.4%, 92.4%, and 92.6% for the DBD‐SLK group, P = 0.3 for all). The DCD‐SLK group had worse patient, liver graft, and kidney graft survival at 3 years (62.5%, 62.5%, and 58.9% versus 90.5%, 90.5%, and 90.6%, P = 0.03 for all) and at 5 years (62.5%, 62.5%, and 58.9% versus 87.4%, 87.4%, and 87.7%, P < 0.05 for all). An analysis of the Organ Procurement and Transplantation Network database showed inferior 1‐ and 5‐year patient and graft survival rates for DCD‐SLK patients versus DBD‐SLK patients. In conclusion, despite comparable rates of surgical and medical complications and comparable kidney function at 1 year, DCD‐SLK transplantation was associated with inferior long‐term survival in comparison with DBD‐SLK transplantation. Liver Transpl 20:728‐735, 2014. © 2014 AASLD.